The Influence of Waiter Quality, Price and Taste on Customer Satisfaction at Salamae Tolitoli Restaurant: Pengaruh Kualitas Pelayan, Harga Dan Cita Rasa Terhadap Kepuasan Pelanggan Pada Rumah Makan Salamae Tolitoli - Usman, Nurhidayah; Fitriani, Yuliani (STIE MUJAHIDIN TOLITOLI, 2025)
This study aims to determine the influence of service quality, price and taste on customer satisfaction at the salamae Tolitoli restaurant. This study uses quantitative research using an associative approach. The results of this study show that the variable of service quality partially has a positive and significant effect on customer satisfaction. Price variables partially have a positive and significant effect on customer satisfaction. The taste variable partially has a positive and significant effect on customer satisfaction and together the quality of service, price, and taste simultaneously have a positive and significant effect on customer satisfaction at the salamae Tolitoli restaurant. The results of the t-test showed that the three variables partially had a significant effect, while the f-test proved the effect simultaneously. Square's R-value of 0.506 indicates that 50.6% of the variation in customer satisfaction can be explained by all three variables. The remaining 49.4% was influenced by other factors outside the model. The Adjusted R Square value of 0.489 indicates that the model is quite good despite adjustments to the number of variables.